Grain dust explosions decline in 1982 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
The number of grain dust explosions in the U.S. dropped sharply during 1982 according to statistics collected by Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. These data were assembled throughout the year in cooperation with the individual firms and Mike Lyman, USDA-FGIS, Safety Director and OSHA personnel. There were 14 reported explosions in 1982 compared to 21 in 1981 and a peak of 44 in 1980. The 10 year average is 19.
Keywords: Grain dust; Dust explosions